(untitled) (Princeton, 1971)
Contents: Choice and consequence; Political and military: The bureaucracy as a political force, 1920-45; Retrogression in Japan's foreign policy decision-making process; The failure of military expansionism; The radical Left and the failure of communism; Economic and social: Rural origins of Japanese fascism...
Keywords: Japan,Nhật Bản; Economic conditions,Điều kiện kinh tế